Peran Orang Tua dalam Upaya Meningkatkan Literasi Membaca Siswa Sekolah Alam - Brillianing Pratiwi; Rahma Dewi Hartati; Muhammad Sulaiman (Publikasi Pendidikan, 2023)
The problem that exists in Sekolah Alam Kebun Tumbuh is that the level of children's reading interest in reading books is lacking, so it is necessary to socialize reading literacy which is followed up by optimizing reading literacy activities and it is hoped that student literacy will appear in reading.The purpose of this service is to develop reading literacy in kindergarten children of Sekolah Alam Kebun Tumbuh. This method of devotion uses three activities, namely reading aloud, sticking pictures, and mixing colors. In addition, this activity also aims to establish learning collaboration between teachers and parents when teaching students.  The conclusion of this dedication is the activity of developing reading literacy into good stimulation for students in increasing learning motivation. Another good result that also emerged was the growth of courage in displaying creations to others.